O perfil das mulheres religiosas em Cantigas de Santa Maria e miniaturas : estudo da relação entre texto e imagem - Silveira, Josilene Moreira (2009)
In the Cantigas de Santa Maria, by Afonso X, there are innumerable women under different profiles, revealing their addictions, virtues and regrets by the practiced sins, in a continuous search for the salvation of their souls. These aspects are more intense in the miracle narratives that portrait religious women, monks and abbess, where the sin is always haunting the imaginary or those women who fought against it incessantly. The aim of this work is to offer a female profile of six lays of miracle which refer to religious women in the poem e in correspondent illustration. The lays of miracles that compound the selected corpus were taken from the edition organized by Mettmann (1959-1972), while the analyzed miniatures belong to Códice Rico (Escorial, T. I.1). In this analyzes the verbal and non-verbal narratives are considered as a conjoint process of sense production, which derives from the text and the image. Therefore, the problematic of illustration requires a more specific reflection concerned the relation with the poem, based on Aguiar e Silva (1990), Praz (1982), Souriau (1983) e Joly (1996), and in the statute of Medium Age, under the perspectives of Schmitt (2007), Baschet (1996; 2006) and Groulier (2004). Next, it is going to be discussed about the relation between the text and the image in the medieval context, with Schapiro (1998). This study still include the study of Trovadorismo with Tavani (1998; 2002), Vieira (1992), Lapa (1973) e Lopes e Saraiva (1996), and Cantigas de Santa Maria by Leão (1997; 2007), Dominguez e Gajardo (2007), Picaza (2002), Serrano (1987), among others. In the reading of Cantigas de Santa Maria the study of the text and image revealed new aspects in the construction of religious women profile.